Grains and cereals - Hewitt, Sally, 1949- (London : Wayland, 2007)
Explains why grains and cereals are nutritious, describes where they come from, and discusses how to eat, buy, store, and cook them.
Includes index.
2.1
K-3.
K-3
Keywords: Cereal products -- Juvenile literature; Cereals as food -- Juvenile literature; Grain -- Juvenile literature; Cereal products; Cereals as food; Grain; Grain; Prepared cereals